2023
DOI: 10.1002/ajum.12340
|View full text |Cite
|
Sign up to set email alerts
|

Incidental detection of malignancy on point‐of‐care renal ultrasound: A case series

Abstract: Renal point‐of‐care ultrasound (POCUS) is an increasingly common initial imaging modality in the diagnostic workup of renal colic. The primary use of renal POCUS is to assess for hydronephrosis; however, other significant findings suggestive of malignancy can also be identified. We present three cases of unexpected findings identified initially on POCUS in the emergency department, which subsequently led to new diagnoses of malignancy. As renal POCUS becomes more frequently used in clinical practice, physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…And finally, two case studies show the impact on clinical care achieved through POCUS. Adorno et al 5 . present a series of three cases who were being worked up for renal colic, in which emergency room POCUS resulted in the detection of malignant tumours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, two case studies show the impact on clinical care achieved through POCUS. Adorno et al 5 . present a series of three cases who were being worked up for renal colic, in which emergency room POCUS resulted in the detection of malignant tumours.…”
mentioning
confidence: 99%
“…And finally, two case studies show the impact on clinical care achieved through POCUS. Adorno et al 5 present a series of three cases who were being worked up for renal colic, in which emergency room POCUS resulted in the detection of malignant tumours. And Yasuda et al 6 present a case where POCUS revealed free fluid in the abdomen which expedited a CT scan and diagnosis of spontaneous intraperitoneal haemorrhage secondary to gastric vessel rupture in a young patient presenting with chest pain.…”
mentioning
confidence: 99%